Targeting the gut-pancreatic axis: microbial modulation of immunotherapy in pancreatic cancer - Yuan, YuRong; Zhang, Wei; Wang, Deqiang (Frontiers in Immunology, 2026)
With advances in microbial sequencing technology, the role of microorganisms in cancer development and treatment has been increasingly explored. The gut microbiota, as a key shaper of both innate and adaptive immunity, is believed to migrate from the gut and colonize the pancreas, thereby influencing the tumor microenvironment(TME) of pancreatic cancer. Pancreatic cancer exhibits treatment resistance due to its immunosuppressive TME and high interstitial density. Multiple sequencing analyses of pancreatic tumor tissues have revealed that alterations in the tumor-associated microbiota are associated with prognosis and treatment response, suggesting that the microbiota may serve as a complementary modality in immunotherapy. This paper describes potential pathways by which the gut microbiota can migrate to the pancreas and analyzes changes in tumor microbiota composition. It also identifies microbiota types associated with prognosis, and summarizes treatment strategies leveraging the gut-pancreas axis to enhance the personalization and precision of care. It critically examines the limitations of existing research, and aims to leverage microbiome ecology to overcome the immune -suppressive barrier in pancreatic cancer and improve patient outcomes.